4y-6(y+8)=8y+12

Simple and best practice solution for 4y-6(y+8)=8y+12 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 4y-6(y+8)=8y+12 equation:


Simplifying
4y + -6(y + 8) = 8y + 12

Reorder the terms:
4y + -6(8 + y) = 8y + 12
4y + (8 * -6 + y * -6) = 8y + 12
4y + (-48 + -6y) = 8y + 12

Reorder the terms:
-48 + 4y + -6y = 8y + 12

Combine like terms: 4y + -6y = -2y
-48 + -2y = 8y + 12

Reorder the terms:
-48 + -2y = 12 + 8y

Solving
-48 + -2y = 12 + 8y

Solving for variable 'y'.

Move all terms containing y to the left, all other terms to the right.

Add '-8y' to each side of the equation.
-48 + -2y + -8y = 12 + 8y + -8y

Combine like terms: -2y + -8y = -10y
-48 + -10y = 12 + 8y + -8y

Combine like terms: 8y + -8y = 0
-48 + -10y = 12 + 0
-48 + -10y = 12

Add '48' to each side of the equation.
-48 + 48 + -10y = 12 + 48

Combine like terms: -48 + 48 = 0
0 + -10y = 12 + 48
-10y = 12 + 48

Combine like terms: 12 + 48 = 60
-10y = 60

Divide each side by '-10'.
y = -6

Simplifying
y = -6

See similar equations:

| 7x^2-10*x-5=0 | | -5+6j=-53 | | -1x+3=19 | | 39=-3+5(x+6) | | 7w+8=64 | | 2x-5=-(3x+7) | | 3=-6x+3(x+3) | | 19-3x=9x-5 | | 1.8+7n=4n | | y+6=5x+3xr-4 | | 9-3p=3 | | 7x+-3=-11 | | 2-7x=5x+50 | | 2x=-(3x+7) | | 25m-10=21m+14 | | 10y-7=28+3y | | -122+2x=153-9x | | 8-3w=5 | | 3x-14=-5x+34 | | 16=7b+30 | | 0.70x=455000 | | 3u-12=-21 | | 4*7v= | | 8y-3=-27 | | 3z^2+3z+1=0 | | 2x^2-3x-72=0 | | 30y^2=36y | | 2(a-8)+7=5(a+2)-3a-29 | | 9x-45=5x+135 | | (2)(5)+4= | | -3x-9+8x=12x+9-7x | | solvea+4=10 |

Equations solver categories